Innovation in high-performance sports medicine - Speed, C. A.; Roberts, W. O. (British Journal of Sports Medicine, 2011)
High-performance sports medicine (HPSM) is an area of sport and exercise medicine (SEM) that deals with distinct groups of individuals who can differ from the general population in many ways, including their physiology, psychology and behaviour. As detailed in the first article of this series, provision of medical care to the high-performance athlete can involve specific and often unconventional models of working to facilitate the delivery of optimum medical care to the athlete and team. This is still an evolving area, and the best models of care will vary between sports, athletes and nations. However, the evidence base relating to best-practice medical care in the elite athlete population is currently lacking. Unproven and at times inappropriate approaches are common in HPSM, and athletes must be protected from these. While research issues form the subject of the following article, here we discuss the great opportunity—and a necessity—for innovation to help to provide best practice. Innovation is not easy: it requires huge commitment and proactive creativity to explore novel methods and models that suit specific sports. Carefully selected models and methods can then be thoroughly scrutinised through rigorous research. This article focuses upon the nature and process of innovation, and its importance to the development of HPSM. Importantly, many of the examples given also have relevance in the field of SEM in general.